Implementation of a medical distance methodological design in COVID-19 times (SciComm Report, 2021)
The challenge of linking university students in the fight against an emerging, highly contagious disease and the maintenance of the educative process from the First Health Care Settings in COVID, requires didactic alternatives that allow describing the implementation of a methodological design for distance medical education, during the COVID-19 investigation, in the Santo Domingo municipality, Cuba. From the Teaching Department of the Municipal Health Directorate, an advisory group was formed that carried out —based on the theoretical references established through a digital search in national and international sites— the proposal of an integrated model for the pre and post graduated distance education taking into account the b-learning and m- learning. In the model design it was considered the pedagogical, organizational, technological and that of the quality evaluation components. After the proposal implementation it was created a virtual community for health teaching in the territory which involved the pre and post graduated education. The indicators reached in both alternatives were very satisfactory, it was possible to promote all the students which belonged to the model with a high satisfaction level, it was evident the reinforcement of values like freedom, creativity, cooperation, and partnership. Both, students, and professors accepted and reached the goal. The designed Project guaranteed the continuation of the Educative Learning process until its fulfillment with satisfactory results to the pre and post graduate   medical education, the experience made possible to improve and broaden the professional growth in the territory and to establish a precedent for future interventions.
Keywords: distance education; pedagogical model; covid-19; medical education